Comparing the Mini-BESTest with the Berg Balance Scale to Evaluate Balance Disorders in Parkinson's Disease - Laurie A. King; Kelsey C. Priest; Arash Salarian; Don Pierce; Fay B. Horak (Parkinson's Disease)
Objective. The purpose of this study was to explore the usefulness of the Mini-BESTest compared to the Berg Balance Scale in evaluating balance in people with PD of varying severity. We evaluated (1) the distribution of patients scores to look for ceiling effects, (2) concurrent validity with severity of disease, and (3) the sensitivity/specificity of separating people with or without postural response deficits. Subjects. Ninety-seven people with PD were tested for balance deficits using the Berg, Mini-BESTest, Unified Parkinson’s Disease Rating Scale (UPDRS) III and the Hoehn & Yahr (H&Y) disease severity classification. Setting. Clinical research facility at Oregon Health & Science University. Results. The Mini-BESTest is highly correlated with the Berg (r=0.79, P<0.001), but avoids the ceiling compression effect of the Berg for mild PD (skewness −2.30 Berg, −0.93 Mini-BESTest). Consequently, the Mini-BESTest is more effective than the Berg for predicting UPDRS Motor score (P<0.001 Mini-BESTest versus P=0.86 Berg), and for discriminating between those with and without postural response deficits as measured by the H&Y (ROC differential P=0.06). Conclusion. The Mini-BESTest is a promising tool for discerning balance deficits in patients with PD, most importantly those with more subtle deficits.